Age-Related Changes in Neuron–Microglia Interaction Mediated by Fractalkine Under Inflammatory Conditions - Eugenin-Leon, J (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Ageing results in an increased microglial activation and neuroinflammation. We are interested in assessing ageing-dependent changes in the amount and fractalkine (CX3CL1) proteoforms participating in neuron–microglia crosstalk that could be involved in microglia activation. We analysed age-dependent changes in CX3CL1, CX3CR1, and TGFβ mRNAs using RT-qPCR and CX3CL1 proteoforms using Western blot, in 3 to 20-month-old WT mice and an inflammatory mouse model (SRA−/−) treated with 0.5 mg/kg of intraperitoneal LPS, 2 ng of intrathecal TGFβ, or a vehicle. CX3CL1, CX3CR1, and TGFβ were affected by ageing. CX3CL1 mRNA was similar in young and adult mice but decreased by 52% in >20-month-old mice; adult mice showed a 3-fold increase in 70 kDa soluble CX3CL1. CX3CR1 showed a progressive increase, reaching a 2-fold increase in >20-month-old mice. TGFβ expression and cytokine reached their highest levels (3-fold increase) in adult mice and were reduced by 45% in >20-month-old mice. Inflammation, especially in SRA−/− mice, produced an increase in CX3CL1 mRNA in adult mice and a maximal CX3CR1 mRNA level in old mice, which were nearly abolished by TGFβ. Our findings show age-related changes in CX3CL1 and TGFβ, with the highest levels observed in adult mice, an age at which the early mechanisms leading to neurodegenerative disease initiate. © 2025 by the authors.